THE INFLUENCE OF JOB ANALYSIS AND EDUCATION ON IMPROVING EMPLOYEE PERFORMANCE THROUGH CAREER DEVELOPMENT IN THE STATE CIVIL APPARATUS IN EAST LUWU REGENCY - Anita; Salju; Goso; Rahmawati, (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2024)
This research examines the influence of job analysis and education on the State Civil Apparatus (ASN) performance in East Luwu Regency, with career development as an intervening variable. The observed phenomenon shows that the performance of ASN in East Luwu Regency is not yet optimal, allegedly caused by a lack of proper job analysis, low levels of education, and not yet optimal career development. The research method used is a quantitative approach with a survey design. The research sample consisted of 100 ASNs selected from various government agencies in East Luwu Regency. Data was collected using a questionnaire tested for validity and reliability. Data analysis used Structural Equation Modeling (SEM) techniques to test the direct and indirect relationship between job analysis, education, career development, and performance. The research results show that job analysis positively and significantly influences improving performance but not significantly on career development. Education has a positive and significant effect on career development but not significantly on enhancing performance. Directly, career development has a positive and significant impact on improving performance. Job analysis has a positive but not significant effect on improving performance through career development. However, career development significantly influences the relationship between education and performance improvement in East Luwu Regency.